Measurement of the polarization of the upsilon(1S) and upsilon(2S) states in pp collisions at square root[s]=1.96 TeV. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
We present a study of the polarization of the Upsilon(1S) and Upsilon(2S) states using a 1.3 fb;{-1} data sample collected by the D0 experiment in 2002-2006 during run II of the Fermilab Tevatron Collider. We measure the polarization parameter alpha=(sigma_{T}-2sigma_{L})/(sigma_{T}+2sigma_{L}), where sigma_{T} and sigma_{L} are the transversely and longitudinally polarized components of the production cross section, as a function of the transverse momentum (p_{T};Upsilon) for the Upsilon(1S) and Upsilon(2S). Significant p_{T};Upsilon-dependent longitudinal polarization is observed for the Upsilon(1S). A comparison with theoretical models is presented.